Tuberculosis Arthritis: A Diagnostic Challenges - Desak Putu Gayatri Saraswati Seputra (Indonesian Rheumatology Associantion, 2023)
Background: Tuberculosis infection still poses a significant health problem,especially in developing countries. While most of tuberculosis cases affectthe pulmonary organ, this infection may also involve other organs such asbones and joints. Case presentation: We reported a case of 23-year-oldfemale patient with a history of recurrent pain and swelling in the right knee. On physical examination of the right knee, bulging sign was found,accompanied by tenderness, warmth on palpation, and limited active and passive movement. Radiographic examination was suggestive for septicarthritis in the right knee. Debridement and biopsy were performed, and TBPCR examination of the debridement tissue was found to be positive forMycobacterium tuberculosis. The histopathological finding was alsoconsistent with tuberculosis infection. The patient was subsequently treatedwith antituberculosis drugs and underwent rehabilitation therapy, resultingin a satisfying response. Conclusion: Diagnosis of tuberculosis arthritis inthis case was established based on the presence of clinical symptoms, radiological findings, tissue TB PCR, and histopathological findings. Both surgical and pharmacological interventions were performed, which yieldedfavorable results. Tuberculosis arthritis was often misdiagnosed as arthritis for other causes, resulting in delays in providing medical intervention.Therefore, increased understanding of tuberculosis arthritis is necessary tofacilitate early diagnosis and improve therapeutic outcome.